The Effect of Regulations on Using Disposable Plastic in Community and Tourism Behaviors in Denpasar, Bali - Agustina, Arik; Aprinica, Ni Putu Isha (Journal of Business on Hospitality and Tourism, 2021)
Plastic waste have been a problem for the sustainability of tourism, especially Bali. Efforts to reduce plastic waste have been carried out by the government, such as the issuance of Denpasar Mayor Regulation Number 36 of 2018 and then followed by Bali Governor Regulation Number 97 of 2018. This paper aims to find out the opinions and changes in behavior of Balinese people, especially in Denpasar City after the enactment of the Denpasar Mayor Regulation and the Bali Governor Regulation about plastic waste. Data collection carried out through questionnaires distributed to tourists, students (tourism department), traders, the general public, and Lecturer. The result is everyone is aware of the government regulation on limiting single-use plastic bags, but some residents only know about the existence of government regulations without knowing where the regulations came from. Most of the people agree with the policy, but there are also people who disagree because the use of plastic bags is more efficient, however. This policy has led people to cultivate bringing their shopping bags.